STRATEGI PENGUATAN EMPATI DALAM MENANGGULANGI PERUNDUNGAN SISWA DI SDN SUCOPANGEPOK - Hariyanto Hariyanto; Ellan Rachmawatie (KARYA: Jurnal Pengabdian Kepada Masyarakat, 2026)
This research is motivated by the prevalence of bullying phenomena at SDN Sucopangepok, which generally manifests as covert verbal and relational violence, thus presenting challenges for teachers in early detection. This research aims to analyze the forms and impacts of the bullying, while also examining the process of implementing empathy character strengthening strategies to prevent and identify it. This research uses a qualitative approach with a descriptive case study design, where the research subjects are determined thru purposive sampling, including school principals, class teachers, and students. Data collection was carried out using triangulation techniques thru field observations, in-depth interviews, and documentation, then analyzed using an interactive model and validated with source and technique triangulation. The research findings reveal that verbal and relational bullying at the school have a significant destructive impact on children psychologically, socially, and academically. To address this issue, the school implemented an empathy reinforcement program that integrates storytelling methods to stimulate cognitive empathy, role-playing for affective empathy, and positive reinforcement thru the "Empathy Tree" system. In conclusion, this integrated strategy has proven effective in reducing the incidence of bullying, transforming the apathy of bystanders into assertive defensive actions, and significantly enhancing teachers' capacity to detect early signs of bullying.